In silico identification of immunotherapeutic and diagnostic targets in the glycosylphosphatidylinositol metabolism of the coccidian Sarcocystis aucheniae - Decker Franco, Cecilia (2020)
Meat of the South American camelids (SACs) llama and alpaca is an important source of animal protein and income for rural families in the Andes, and a product with significant growth potential for local and international markets. However, infestation with macroscopic cysts of the coccidian protozoon Sarcocystis aucheniae, a parasitosis known as SAC sarcocystosis, significantly hampers its commercialization. There are no validated methods to diagnose the presence of S. aucheniae cysts other than carcass examination. Moreover, there are no available drugs or vaccines to cure or prevent SAC sarcocystosis. Identification of relevant molecules that act at the host–pathogen interface can significantly contribute to the control of this disease. It has been shown for other pathogenic protozoa that glycosylphosphatidylinositol (GPI) is a critical molecule implicated in parasite survival and pathogenicity. This study focused on the identification of the enzymes that participate in the S. aucheniae GPI biosynthetic pathway and the repertoire of the parasite GPI‐anchored proteins (GPI‐APs). To this aim, RNA was extracted from parasite cysts and the transcriptome was sequenced and translated into amino acid sequences. The generated database was mined using sequences of well‐characterized GPI biosynthetic enzymes of Saccharomyces cerevisiae and Toxoplasma gondii. Eleven enzymes predicted to participate in the S. aucheniae GPI biosynthetic pathway were identified. On the other hand, the database was searched for proteins carrying an N‐terminal signal peptide and a single C‐terminal transmembrane region containing a GPI anchor signal. Twenty‐four GPI‐anchored peptides were identified, of which nine are likely S. aucheniae‐specific, and 15 are homologous to membrane proteins of other coccidians. Among the latter, 13 belong to the SRS domain superfamily, an extensive group of coccidian GPI‐anchored proteins that mediate parasite interaction with their host. Phylogenetic analysis showed a great degree of intra‐ and inter‐specific divergence among SRS family proteins. In vitro and in vivo experiments are needed to validate S. aucheniae GPI biosynthetic enzymes and GPI‐APs as drug targets and/or as vaccine or diagnostic antigens.